Zeitungsstil - Wille, Manuel (Wörterbücher zur Sprach- und Kommunikationswissenschaft (WSK) Online, edited by Stefan J. Schierholz.)

So Far...From Now On # 6. - Jacke, Christoph (Die Aufhebung)

Statistical and Neural Network Based Speech Activity Detection in Non-Stationary Acoustic Environments - Heitkaemper, Jens; Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (INTERSPEECH 2020 Virtual Shanghai China)
Speech activity detection (SAD), which often rests on the fact that the noise is "more'' stationary than speech, is particularly challenging in non-stationary environments, because the time variance of the acoustic scene makes it difficult to discriminate speech from noise. We propose two approaches to SAD, where one is based on statistical signal processing, while the other utilizes neural networks. The former employs sophisticated signal processing to track the noise and speech energies and is meant to support the case for a resource efficient, unsupervised signal processing approach. The latter introduces a recurrent network layer that operates on short segments of the input speech to do temporal smoothing in the presence of non-stationary noise. The systems are tested on the Fearless Steps challenge database, which consists of the transmission data from the Apollo-11 space mission. The statistical SAD achieves comparable detection performance to earlier proposed neural network based SADs, while the neural network based approach leads to a decision cost function of 1.07% on the evaluation set of the 2020 Fearless Steps Challenge, which sets a new state of the art.
Keywords: voice activity detection; speech activity detection; neural network; statistical speech processing

When entrepreneurs become leaders: how entrepreneurs deal with people management - Hubner-Benz, Sylvia (International Journal of Entrepreneurial Venturing)
Keywords: Management of Technology and Innovation; Strategy and Management; Business and International Management

Hustlers, hipsters and hackers: Potential employees’ stereotypes of entrepreneurial leaders - Rudic, Biljana; Hubner-Benz, Sylvia; Baum, Matthias (Journal of Business Venturing Insights)
Keywords: Management of Technology and Innovation; Business and International Management

Perceptions of the Self Versus One’s Own Social Group: (Mis)conceptions of Older Women’s Interest in and Competence With Technology - Gales, Alina; Hubner-Benz, Sylvia (Frontiers in Psychology)
Keywords: General Psychology

Political embeddedness and firms’ choices of earnings management strategies in China - Wang, Zhi; Braam, Geert; Reimsbach, Daniel; Wang, Jiaxin (Accounting & Finance)
Abstract We examine whether and how political embeddedness influences financial reporting quality in China by investigating how government ownership and political connections affect Chinese listed firms’ choices of earnings management strategies. The results show that state‐owned enterprises (SOEs), and in particular, central SOEs, are more likely to substitute accrual‐based earnings management strategies with costlier but less detectable real earnings management strategies than non‐SOEs. The results also indicate that politically connected enterprises (PCEs) are more likely to employ less detectable real earnings management strategies than non‐PCEs, so much so that PCEs’ total earnings management level is higher than that of non‐PCEs.
Keywords: Economics; Econometrics and Finance (miscellaneous); Finance; Accounting

Bringing Signaling Theory to Intermediated Voluntary Disclosure. Commentary on “Detecting False Accounts in Intermediated Voluntary Disclosure” by Patrick Callery and Jessica Perkins - Hahn, Rüdiger; Reimsbach, Daniel (Academy of Management Discoveries)

Enhancing Fifth Graders’ Awareness of Syntactic Features in Mathematical Word Problems: A Design Research Study on the Variation Principle - Dröse, Jennifer; Prediger, Susanne (Journal für Mathematik-Didaktik, 41(2))

Symmetry in optimal control: A multiobjective model predictive control approach - Flaßkamp, K.; Ober-Blöbaum, Sina; Peitz, S. (Advances in Dynamics, Optimization and Computation)

"Dein jüdisches Gesicht". Zu drei Gedichten des "Ilana"-Zyklus von Paul Celan - Spener, Anna Maria (Celan-Jahrbuch 11)

Automatisierung der motorischen Kontrolle - Krause, Daniel; Blischke, Klaus (Bewegung, Training, Leistung und Gesundheit)

Is it still worth it? Applying expectancy-value theory to investigate the intraindividual motivational process of forming intentions to drop out from university - Schnettler, Theresa; Bobe, Julia; Scheunemann, Anne; Fries, Stefan; Grunschel, Carola (Motivation and Emotion)
Abstract The intraindividual process of study dropout, from forming dropout intention to deregistration, is of motivational nature. Yet typical studies investigate interindividual differences, which do not inform about intraindividual processes. Our study focused on the intraindividual process of forming dropout intention, and applied expectancy-value theory to analyze its motivational underpinnings. To expand research, we considered associations of intraindividual deviations in expectancy, intrinsic value, attainment value, utility value, and cost to intraindividual deviations in dropout intention. A total of 326 undergraduate students of law and mathematics rated motivational variables and dropout intention three times from semester start to the final exam period. Multilevel regression analyses revealed that intraindividual changes in intrinsic value, attainment, and cost, but not in expectancy and utility, related to intraindividual changes in dropout intention. Further, we considered students’ demographics as moderators. Only age moderated the association between intrinsic value and dropout intention. Our results stress the crucial role of certain value components, including cost, for emerging dropout intention.
Keywords: Experimental and Cognitive Psychology; Social Psychology

End-to-End Training of Time Domain Audio Separation and Recognition - von Neumann, Thilo; Kinoshita, Keisuke; Drude, Lukas; Boeddeker, Christoph; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (ICASSP 2020 - 2020 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP))
The rising interest in single-channel multi-speaker speech separation sparked development of End-to-End (E2E) approaches to multispeaker speech recognition. However, up until now, state-of-theart neural network–based time domain source separation has not yet been combined with E2E speech recognition. We here demonstrate how to combine a separation module based on a Convolutional Time domain Audio Separation Network (Conv-TasNet) with an E2E speech recognizer and how to train such a model jointly by distributing it over multiple GPUs or by approximating truncated back-propagation for the convolutional front-end. To put this work into perspective and illustrate the complexity of the design space, we provide a compact overview of single-channel multi-speaker recognition systems. Our experiments show a word error rate of 11.0% on WSJ0-2mix and indicate that our joint time domain model can yield substantial improvements over cascade DNN-HMM and monolithic E2E frequency domain systems proposed so far.

Multi-Talker ASR for an Unknown Number of Sources: Joint Training of Source Counting, Separation and ASR - von Neumann, Thilo; Boeddeker, Christoph; Drude, Lukas; Kinoshita, Keisuke; Delcroix, Marc; Nakatani, Tomohiro; Haeb-Umbach, Reinhold (Proc. Interspeech 2020)
Most approaches to multi-talker overlapped speech separation and recognition assume that the number of simultaneously active speakers is given, but in realistic situations, it is typically unknown. To cope with this, we extend an iterative speech extraction system with mechanisms to count the number of sources and combine it with a single-talker speech recognizer to form the first end-to-end multi-talker automatic speech recognition system for an unknown number of active speakers. Our experiments show very promising performance in counting accuracy, source separation and speech recognition on simulated clean mixtures from WSJ0-2mix and WSJ0-3mix. Among others, we set a new state-of-the-art word error rate on the WSJ0-2mix database. Furthermore, our system generalizes well to a larger number of speakers than it ever saw during training, as shown in experiments with the WSJ0-4mix database.

Gedenken an Luftangriffe auf Paderborn: "Erinnerung wird nie obsolet sein" - Hartung, Olaf (Neue Westfälische)

Workshops zur geschichtsdidaktischen Lehre in Zeiten von Corona - Hartung, Olaf (Paderborner Universitätszeitschrift)

Deep Neural Network based Distance Estimation for Geometry Calibration in Acoustic Sensor Network - Gburrek, Tobias; Schmalenstroeer, Joerg; Brendel, Andreas; Kellermann, Walter; Haeb-Umbach, Reinhold (European Signal Processing Conference (EUSIPCO))
We present an approach to deep neural network based (DNN-based) distance estimation in reverberant rooms for supporting geometry calibration tasks in wireless acoustic sensor networks. Signal diffuseness information from acoustic signals is aggregated via the coherent-to-diffuse power ratio to obtain a distance-related feature, which is mapped to a source-to-microphone distance estimate by means of a DNN. This information is then combined with direction-of-arrival estimates from compact microphone arrays to infer the geometry of the sensor network. Unlike many other approaches to geometry calibration, the proposed scheme does only require that the sampling clocks of the sensor nodes are roughly synchronized. In simulations we show that the proposed DNN-based distance estimator generalizes to unseen acoustic environments and that precise estimates of the sensor node positions are obtained.

Corporate Entrepreneurship: Die Rolle und Bedeutung des Humankapitals - Krebs, Benjamin; Kabst, Rüdiger (PERSONALquartely)

Corporate Entrepreneurship durch die Allokation von Ressourcen - Megow, N.; Kabst, Rüdiger (Perspektiven des Entrepreneurships: Unternehmerische Konzepte zwischen Theorie und Praxis)

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie; Furman, Susanne; Acar, Yasemin

Smart Home Security and Privacy Mitigations: Consumer Perceptions, Practices, and Challenges - Haney, Julie M.; Furman, Susanne M.; Acar, Yasemin (HCI for Cybersecurity, Privacy and Trust)

Cloudy with a Chance of Misconceptions: Exploring Users’ Perceptions and Expectations of Security and Privacy in Cloud Office Suites - Wermke, Dominik; Huaman, Nicolas; Stransky, Christian; Busch, Niklas; Acar, Yasemin; Fahl, Sascha (Sixteenth Symposium on Usable Privacy and Security, SOUPS 2020, August 7-11, 2020)

Listen to Developers! A Participatory Design Study on Security Warnings for Cryptographic APIs - Gorski, Peter Leo; Acar, Yasemin; Lo Iacono, Luigi; Fahl, Sascha (Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems)

Gier und andere Tugenden: Widersprüchliche Bewertungen der Marktwirtschaft in Oliver Stones Wall Street - Schneider, Martin (Erzähltes Geld Finanzmärkte und Krisen in Literatur, Film und Medien)

Urbane Arbeitsparadiese gestern und heute - Schneider, Martin (Urbane Kulturen und Räume Intermedial)

Personalwirtschaft - Schneider, Martin; Eisele, Simon (Handbuch Gestaltung digitaler und vernetzter Arbeitswelten)

Is Corruption Imprinted? A Study on Preconditions of Corruption in Post-Communist Countries - Knorr, Karin; Auer, Thorsten Fabian; Thommes, Kirsten (Academy of Management Proceedings)

»die reine farben- formen- und linienfreude«. Zur Vision einer ›reinen Formkunst‹ in den ornamentalen Konstellationen der Blätter für die Kunst - Gretz, Daniela (Formästhetiken und Formen der Literatur. Materialität – Ornament – Codierung)

Expertise von Lehrpersonen für inklusiven Mathematikunterricht der Sekundarstufe - Ausgangspunkte zur Professionalisierungsforschung. - Seitz, Susanne; Häsel-Weide, Uta; Wilke, Yannik; Wallner, Melina (K:ON Kölner Online-Journal für Lehrer*innenbildung)

Wolfgang Weber (1939–2019) Professor of Human Resource Management and Founding Editor of the German Journal of Human Resource Management - Festing, Marion; Iseke, Anja; Kabst, Rüdiger; Martin, Albert; Matiaske, Wenzel; Mayrhofer, Wolfgang; Nienhüser, Werner (German Journal of Human Resource Management: Zeitschrift für Personalforschung)

Intergenerational Value Similarity in Adulthood - Hoellger, Christian; Sommer, Sabrina; Albert, Isabelle; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on value similarity between parents and their children during adulthood. The interplay between gender, age, relationship quality, and frequency of contact on value similarity was analyzed. A total of 600 adult German children (53.8% women) and their parents took part in a questionnaire study. Value orientation was measured with a short version of Schwartz’s Portrait Values Questionnaire, and relationship quality with the Network of Relationships Inventory (Furman & Buhrmeister, 1992).Value similarity was higher in mother–daughter dyads compared to mother–son dyads, but in the other dyads, no significant differences were found. Regarding relationship quality, verbal intimacy was not related to value similarity. Parental satisfaction was associated with value similarity in the father–child dyads. Satisfaction, as perceived by adult children, was linked to value similarity in mother–child and father–son dyads. Furthermore, the frequency of contact related to value similarity between mothers and sons.
Keywords: Social Sciences (miscellaneous)

Ecken, Systeme, Funktionsbereiche. Eine Medienkulturgeschichte des Filter(n)s im Kontext von Wohnräumen - Miggelbrink, Monique (Navigationen – Zeitschrift für Medien- und Kulturwissenschaften, Themenschwerpunkt: Filter(n) – Geschichte Ästhetik Praktiken)

Nash Smoothing on the Test Bench: H_alpha--Essential Equilibira - Duman, Papatya; Trockel, Walter

Mental body rotation with egocentric and object-based transformations in different postures: sitting vs. standing - Budde, Kirsten; Barela, José Angelo; Figueiredo, Gabriella Andreeta; Weigelt, Matthias (Brazilian Journal of Motor Behavior)
BACKGROUND: A detail of previous studies on mental rotation, which has not received any attention so far, relates to the testing situation of the participants. In nearly every study, participants were tested in a sitting posture (and not standing). However, when considering embodied cognition approaches on mental processes, participants may not be able to fully exploit these processes when performing mental rotation tasks in a sitting posture.
AIM: Therefore, the aim of the present study is to examine the potential influence of two different postures (sitting vs. standing), when solving mental body rotation tasks.
METHOD: Sixteen participants (6 females) were tested in two mental body-rotation tasks (MBRT), requiring either an object-based spatial transformation (based on a same-different judgment) or an egocentric transformation (based on a left-right judgment) in a sitting and in a standing posture. Reaction times and response errors were analysed in two three-way ANOVAs, with the factors orientation, task, and posture.
RESULTS: Results revealed an effect of orientation and task, indicating that participants performed better for egocentric than for object-based transformations. However, there was no effect of posture.
CONCLUSION: The different dynamics of postural control during sitting and standing do not induce different embodiment effects on mental rotation.

Hat die Körperposition (sitzen vs. stehen) einen Einfluss auf die Leistung in einer Mentalen Rotationsaufgabe? - Budde, Kirsten; Barela, José A; Weigelt, Matthias (Abstractband der 52. Jahrestagung der Arbeitsgemeinschaft für Sportpsychologie (asp))

Linguistik des Briefs - Schuster, Britt-Marie (Handbuch Brief. Von der Frühen Neuzeit bis zur Gegenwart (Bd. 1: Interdisziplinarität – Systematische Perspektiven – Briefgenres))
Keywords: Textsortengeschichte

The contribution of terminology research to the understanding of science communication - Schuster, Britt-Marie (Science Communication (Handbooks of Communication Science))
Keywords: Fachkommunikation

Was bedeutet Ehre? Diskursethische Überlegungen zu den BBC-Reden Thomas Manns - Schuster, Britt-Marie; Markewitz, Friedrich; Wilk, Nicole M. (Diskurs – ethisch.)
Keywords: Textsemantik

micro-Raman Investigations of Periodically-Poled X-Cut Thin-Film Lithium Niobate for Integrated Optics - Reitzig, Sven; Rüsing, Michael; Kirbus, Benjamin; Gossel, Joshua; Singh, Ekta; Eng, Lukas M.; Zhao, Jie; Mookherjea, Shayan (2020 Joint Conference of the IEEE International Frequency Control Symposium and International Symposium on Applications of Ferroelectrics (IFCS-ISAF))

Selbstreguliertes Lernen - Können die das überhaupt? Gestaltung von Lernprozessen in berufsvorbereitenden Bildungsgängen. - Sloane, Peter F. E.; Daniel, Desiree; Meier, Karin; Schwabl, Franziska; Volgmann, Simone

Per-Instance Configuration of the Modularized CMA-ES by Means of Classifier Chains and Exploratory Landscape Analysis - Prager, Raphael Patrick; Trautmann, Heike; Wang, Hao; Bäck, Thomas H. W.; Kerschke, Pascal (Proceedings of the IEEE Symposium Series on Computational Intelligence (SSCI))
In this paper, we rely on previous work proposing a modularized version of CMA-ES, which captures several alterations to the conventional CMA-ES developed in recent years. Each alteration provides significant advantages under certain problem properties, e.g., multi-modality, high conditioning. These distinct advancements are implemented as modules which result in 4608 unique versions of CMA-ES. Previous findings illustrate the competitive advantage of enabling and disabling the aforementioned modules for different optimization problems. Yet, this modular CMA-ES is lacking a method to automatically determine when the activation of specific modules is auspicious and when it is not. We propose a well-performing instance-specific algorithm configuration model which selects an (almost) optimal configuration of modules for a given problem instance. In addition, the structure of this configuration model is able to capture inter-dependencies between modules, e.g., two (or more) modules might only be advantageous in unison for some problem types, making the orchestration of modules a crucial task. This is accomplished by chaining multiple random forest classifiers together into a so-called Classifier Chain based on a set of numerical features extracted by means of Exploratory Landscape Analysis (ELA) to describe the given problem instances.

A Two-Phase Framework for Detecting Manipulation Campaigns in Social Media - Assenmacher, D; Clever, L; Pohl, JS; Trautmann, Heike; Grimme, C (Proceedings of the International Conference on Human-Computer Interaction (HCII 2020): Social Computing and Social Media. Design, Ethics, User Behavior, and Social Network Analysis)
The identification of coordinated campaigns within Social Media is a complex task that is often hindered by missing labels and large amounts of data that have to be processed. We propose a new two-phase framework that uses unsupervised stream clustering for detecting suspicious trends over time in a first step. Afterwards, traditional offline analyses are applied to distinguish between normal trend evolution and malicious manipulation attempts. We demonstrate the applicability of our framework in the context of the final days of the Brexit in 2019/2020.

Towards Automated Configuration of Stream Clustering Algorithms - Carnein, Matthias; Trautmann, Heike; Bifet, Albert; Pfahringer, Bernhard (Proceedings of the European Conference on Machine Learning and Principles and Practice of Knowledge Discovery in Databases (ECMLPKDD ’19))
Clustering is an important technique in data analysis which can reveal hidden patterns and unknown relationships in the data. A common problem in clustering is the proper choice of parameter settings. To tackle this, automated algorithm configuration is available which can automatically find the best parameter settings. In practice, however, many of our today’s data sources are data streams due to the widespread deployment of sensors, the internet-of-things or (social) media. Stream clustering aims to tackle this challenge by identifying, tracking and updating clusters over time. Unfortunately, none of the existing approaches for automated algorithm configuration are directly applicable to the streaming scenario. In this paper, we explore the possibility of automated algorithm configuration for stream clustering algorithms using an ensemble of different configurations. In first experiments, we demonstrate that our approach is able to automatically find superior configurations and refine them over time.

Inside the tool set of automation: Free social bot code revisited - Assenmacher, Dennis; Frischlich , Lena; Trautmann, Heike; Grimme, Christian; Adam, Lena (Disinformation in open online media)
Social bots have recently gained attention in the context of public opinion manipulation on social media platforms. While a lot of research effort has been put into the classification and detection of such automated programs, it is still unclear how technically sophisticated those bots are, which platforms they target, and where they originate from. To answer these questions, we gathered repository data from open source collaboration platforms to identify the status-quo of social bot development as well as first insights into the overall skills of publicly available bot code.

confStream: Automated Algorithm Selection and Configuration of Stream Clustering Algorithms - Carnein, Matthias; Trautmann, Heike; Bifet, Albert; Pfahringer, Bernhard (Proceedings of the 14$^th$ Learning and Intelligent Optimization Conference (LION 2020))
Machine learning has become one of the most important tools in data analysis. However, selecting the most appropriate machine learning algorithm and tuning its hyperparameters to their optimal values remains a difficult task. This is even more difficult for streaming applications where automated approaches are often not available to help during algorithm selection and configuration. This paper proposes the first approach for automated algorithm selection and configuration of stream clustering algorithms. We train an ensemble of different stream clustering algorithms and configurations in parallel and use the best performing configuration to obtain a clustering solution. By drawing new configurations from better performing ones, we are able to improve the ensemble performance over time. In large experiments on real and artificial data we show how our ensemble approach can improve upon default configurations and can also compete with a-posteriori algorithm configuration. Our approach is considerably faster than a-posteriori approaches and applicable in real-time. In addition, it is not limited to stream clustering and can be generalised to all streaming applications, including stream classification and regression.

Anytime Behavior of Inexact TSP Solvers and Perspectives for Automated Algorithm Selection - Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Proceedings of the IEEE Congress on Evolutionary Computation (CEC))
The Traveling-Salesperson-Problem (TSP) is arguably one of the best-known NP-hard combinatorial optimization problems. The two sophisticated heuristic solvers LKH and EAX and respective (restart) variants manage to calculate close-to optimal or even optimal solutions, also for large instances with several thousand nodes in reasonable time. In this work we extend existing benchmarking studies by addressing anytime behaviour of inexact TSP solvers based on empirical runtime distributions leading to an increased understanding of solver behaviour and the respective relation to problem hardness. It turns out that performance ranking of solvers is highly dependent on the focused approximation quality. Insights on intersection points of performances offer huge potential for the construction of hybridized solvers depending on instance features. Moreover, instance features tailored to anytime performance and corresponding performance indicators will highly improve automated algorithm selection models by including comprehensive information on solver quality.

Towards Decision Support in Dynamic Bi-Objective Vehicle Routing - Bossek, Jakob; Grimme, Christian; Rudolph, Günter; Trautmann, Heike (Proceedings of the IEEE Congress on Evolutionary Computation (CEC))
We consider a dynamic bi-objective vehicle routing problem, where a subset of customers ask for service over time. Therein, the distance traveled by a single vehicle and the number of unserved dynamic requests is minimized by a dynamic evolutionary multi-objective algorithm (DEMOA), which operates on discrete time windows (eras). A decision is made at each era by a decision-maker, thus any decision depends on irreversible decisions made in foregoing eras. To understand effects of sequences of decision-making and interactions/dependencies between decisions made, we conduct a series of experiments. More precisely, we fix a set of decision-maker preferences D and the number of eras n t and analyze all |D| nt combinations of decision-maker options. We find that for random uniform instances (a) the final selected solutions mainly depend on the final decision and not on the decision history, (b) solutions are quite robust with respect to the number of unvisited dynamic customers, and (c) solutions of the dynamic approach can even dominate solutions obtained by a clairvoyant EMOA. In contrast, for instances with clustered customers, we observe a strong dependency on decision-making history as well as more variance in solution diversity.

Dynamic Bi-Objective Routing of Multiple Vehicles - Bossek, Jakob; Grimme, Christian; Trautmann, Heike (Proceedings of the Genetic and Evolutionary Computation Conference (GECCO ’20))
In practice, e.g. in delivery and service scenarios, Vehicle-Routing-Problems (VRPs) often imply repeated decision making on dynamic customer requests. As in classical VRPs, tours have to be planned short while the number of serviced customers has to be maximized at the same time resulting in a multi-objective problem. Beyond that, however, dynamic requests lead to the need for re-planning of not yet realized tour parts, while already realized tour parts are irreversible. In this paper we study this type of bi-objective dynamic VRP including sequential decision making and concurrent realization of decisions. We adopt a recently proposed Dynamic Evolutionary Multi-Objective Algorithm (DEMOA) for a related VRP problem and extend it to the more realistic (here considered) scenario of multiple vehicles. We empirically show that our DEMOA is competitive with a multi-vehicle offline and clairvoyant variant of the proposed DEMOA as well as with the dynamic single-vehicle approach proposed earlier.

Automated detection of nostalgic text in the context of societal pessimism - Lena, Clever; Frischlich, Lena; Trautmann, Heike; Grimme, Christian (Disinformation in open online media)
In online media environments, nostalgia can be used as important ingredient of propaganda strategies, specifically, by creating societal pessimism. This work addresses the automated detection of nostalgic text as a first step towards automatically identifying nostalgia-based manipulation strategies. We compare the performance of standard machine learning approaches on this challenge and demonstrate the successful transfer of the best performing approach to real-world nostalgia detection in a case study.